2004
DOI: 10.1158/1078-0432.ccr-03-0732
|View full text |Cite
|
Sign up to set email alerts
|

The Acquisition of hMLH1 Methylation in Plasma DNA after Chemotherapy Predicts Poor Survival for Ovarian Cancer Patients

Abstract: Aberrant epigenetic regulation, such as CpG island methylation and associated transcriptional silencing of genes, has been implicated in a variety of human diseases, including cancer. Methylation of genes involved in apoptosis, including the DNA mismatch repair (MMR) gene hMLH1, can occur in tumor models of resistance to chemotherapeutic drugs. However, the relevance for acquired resistance to chemotherapy of patients' tumors remains unsubstantiated. Plasma DNA from cancer patients, including those with ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
152
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(158 citation statements)
references
References 19 publications
5
152
0
1
Order By: Relevance
“…Indeed, studies link MMR deficiency with reduced CR to platinumbased chemotherapy (Fink et al, 1998b;Strathdee et al, 2001;Gifford et al, 2004). In this study, microarray expression data from 54 patients with advanced stage serous EOC, who had received either cisplatin or carboplatin as part of their primary chemotherapeutic treatment, revealed a correlation between a high MLH1 expression in the patients' tumours and increased CR and survival.…”
Section: Discussionmentioning
confidence: 72%
“…Indeed, studies link MMR deficiency with reduced CR to platinumbased chemotherapy (Fink et al, 1998b;Strathdee et al, 2001;Gifford et al, 2004). In this study, microarray expression data from 54 patients with advanced stage serous EOC, who had received either cisplatin or carboplatin as part of their primary chemotherapeutic treatment, revealed a correlation between a high MLH1 expression in the patients' tumours and increased CR and survival.…”
Section: Discussionmentioning
confidence: 72%
“…Several genes involved in apoptotic pathways related to chemotherapeutic action in ovarian cancer are downregulated by epigenetic mechanisms (Makarla et al, 2005). Methylation of specific genes such as hMLH1 has been shown to correlate with the onset of tumor relapse after carboplatin/taxol therapy in ovarian cancer patients (Gifford et al, 2004). In addition, treatment of cisplatin-resistant A2780/CP ovarian cancer cells with 5-aza-dC induced the expression of hMLH1 and resensitized these cells to cisplatin in a mouse xenograft model (Plumb et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For example, if the Taniguchi model were correct, the predicted effect of the use of nonselective demethylating agents would be to reactivate FANCF expression, and thereby increase cellular resistance to cisplatin. Conversely, Gifford et al (2004) have clearly shown that acquired methylation of hMLH1 is associated with clinical resistance to cisplatin-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%